Participating in Online Museum Communities: An Empirical Study of Taiwan’s Undergraduate Students - Chen, Tien-Li; Lai, Wei-Chun; Yu, Tai-Kuei (Frontiers in Psychology, 2021)
With the worldwide spread of the Internet, human activity has become permeated by digital media which shapes communication and interaction, and speeds up the improvement of the experience and diffusion of museum exhibitions. Contemporary museums must understand their audiences, especially with respect to online preferences and surfing involvement experiences. Museums are changing in an effort to attract young netizens to access and use museum resources. Virtual museums are increasingly using digital exhibitions to preserve and apply their collections, and establishing online community platforms to interact with young people. This study investigates the underlying mechanism of online community characteristics that enhances audiences’ emotional resonance and involvement. Results from a questionnaire survey (N = 1168) of Taiwan undergraduate students show that perceived relevance and esteem improve their emotional resonance, which can attract new people and maintain existing relationships within their communities. Following flow theory, maintaining community relationship characteristics increased emotional resonance, which in turn enhanced user involvement, but we found only small significant effects of emotional resonance on involvement. These findings illuminate the mechanism of the attitudinal relationship building and maintenance for online museum communities, and advance the practical contributions of online museum community use and effects.